Analisis Keterampilan Berpikir Kritis Siswa Kelas XI IPA3 SMA Negeri 1 Anggeraja Melalui Metode Praktikum (Studi pada Materi Titrasi Asam dan Basa) - Kalambo, Intan Elvira; Yunus, Muh; Husain, Halimah (Jurusan Kimia FMIPA UNM, 2021)
This research is descriptive research that aims to analyze the student’s critical thinking skills on acids and bases titration using practical work method. The subjects of this research are 26 students of SMA Negeri 1 Anggeraja class XI IPA3 choosed using random sampling technique. The data was collected by critical thinking test that refers to the five critical thinking indicators of Glaser such as knowing the problem, finding the ways that can be used to solve the problem, gathering and arranging information, analyzing data, and recognizing the connection between the problems. The data was analyzed by descriptive statistic method. The result of this research shows the percentages of student’s critical thinking skills for 5 indicators are; 1) knowing the problem is 85,19% with very high category; 2) finding the ways that can be used to solve the problem is 76,73% with high category; 3) gathering and arranging information is 69,81% with high category; 4) analyzing data is 61,22% with high category; and 5) recognizing the connection between the problems is 45,19% with medium category. In generally, the average of student’s critical thinking skills of SMA Negeri 1 Anggeraja class XI IPA3 on acid bases titration topic using practical work method percentation is 67,63% with high category.